PENGARUH KEPERCAYAAN KONSUMEN TERHADAP DEVELOPER DALAM PELAKSANAAN PERJANJIAN PENGADAAN PERUMAHAN - Helfira Citra; Sry Wahyuni; Yulia Risa (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Consumers often become parties who are positioned as the less powerful, where legal protection for them is so weak and not guaranteed as expected. Indonesia is a developing country that continues to carry out development in all fields, both in the material and spiritual fields, where the development is aimed at realizing the goal of building a just and prosperous society, one of the developments in the material field is to include facilities and infrastructure such as luxury housing developments, medium, even to housing for people (subsidized). Housing or settlements can create a conducive business climate to be able to open a comfortable settlement. The business offer of a house by the developer is sometimes so diverse that the understanding it conveys is not appropriate or not understood (missunderstanding information), meanwhile the prospective buyer sometimes has agreed to even sign his agreement on the binding purchase agreement (PPJB) with the developer so that it has sometimes even arrived at contract stage at a banking institution. This fact further strengthens the high need for housing, even though the realization of the desire to own a residence does not mean that it will always run smoothly.